Direct C–H Arylation of Quinones with Anilines - Lamblin, Marc; Naturale, Guillaume; Dessolin, Jean; Felpin, François-Xavier (Synlett, 2012)
We discovered that anilines were suitable for the direct C–H arylation of benzoquinone in the presence of tert-butyl nitrite. This new reaction proceeds through the in situ formation of a diazonium hydroxide species. The coupling can be carried out at room temperature under neutral, additive-free, metal-free, and aqueous conditions, allowing an environmentally friendly procedure.
Keywords: quinone; aryl diazonium salt; aniline; direct C–H arylation; radical